GERAKAN PROGRESSIF MUHAMMADIYAH DAN NAHDLATUL ULAMA MENJAGA MARWAH PENDIDIKAN KEISLAMAN DI NUSANTARA - Zaitur Rahem (LPPM Institut Agama Islam Al-Hikmah Tuban, 2017)
The Organization of religious and kemasyarkatan in Indnesia very much. Among them is the Muhammadiyah (MD) and Nahdlatul Ulama (NU). Two organization become ordinary broad manevest of religious expressions of Muslims homeland. That's because there has been an assumption, Muhammadiyah and NU has typology amaliyah movement ubudiyah (ritual practices-spriritualis) different. Differences are also evident from the style of movement and organizationally arable land. Muhammadiyah dominate the metropolis, while NU in rural or suburban base. However, despite their ideological and geoorganisatoris typological differences, the two Islamic organizations are able to provide the dedication and outstanding contribution to the civilization of Indonesia. Both were able to stand up and maintain Islamic values ​​typical of the archipelago. In fact, the cadres of both these religious organizations esksist until rentag a very long time. The existence of this organization can be seen from its role in developing the education sector. Key Word: Gerakan Progressif, Muhammadiyah, NU Daftar Rujukan Asy’ari, Suaidi, Nalar Politik NU & Muhammadiyah, (Yogyakarta: LkiS, 2010). John P Miller, Seller Wayne, Curicullum Perpsektif and Praktice, (London: Longman, 1985). Hitty, Philip, History of the Arab, (Jakarta: Serambi, 2016) Kamali, Mohammad Hashim, 2015. Membumikan Syariah, (Jakarta: Mizan, 2015) Lings, Martin, Muhammad, (Jakarta: PT Serambi Ilmu Semesta, 2002) Muzadi, KH. Abdul Muchith, NU dalam Perspektif Sejarah dan Ajaran, (Surabaya: Khalista, 2006). Muhammad Hasyim dan Ahmad Athoillah, Khazanah Katulistiwa: Potret Kehidupan dan Pemikiran Kiai-kiai Nusantara, (Tuban: Kakilangit Book, 2009). Muhaimin, Pengembangan Kurikulum Pendidikan Agama Islam, (Jakarta: PT. Raja Grafindo. 2010). Mun’im Al-Hafni, Abdul, Ensiklopedia Muhammad SAW (Buku Tiga), (Jakarta Selatan: Noura Books, 2014). Muhammad Naquib Al- Attas, Syed, Islam dalam Sejarah dan Kebudayaan Melayu, (Bandung: Mizan, 1990). Nasih Ulwan, Abdullah, Pendidikan Anak dalam Islam, (Jakarta: Pustaka Amani, 2007). Nizar, Samsul, Sejarah Pendidikan Islam: Menelusuri Jejak Sejarah Pendidikan Era Rasulullah Sampai Indonesia, Jakarta: Kencana Prenada Media Group, 2011. Rois, Moh. Fathur, Menyimak Kisah dan Hikmah Kehidupan Nabi Khidir, (Jakarta: Zaman, 2015). Shodiqin, Mochammad Ali, Muhammadiyah Itu NU!, Jakarta: Noura Books, 2013). Smith, Huston. 2016, Agama-agama Manusia, Jakarta: Serambi Soerjabrata, Soemadi, Ichtisar Sejarah Ilmu Jiwa, Yogyakarta: Usma, 1964. Shihab, Quraisy, Membumikan Al-Quran, (Bandung: PT Mizan Pustaka, 2006). Tidjani Djauhari, Mohammad, Pendidikan Untuk Kebangkitan Islam, (Jakarta: TAJ Publishing, 2008). Yatim, Badri , Pengantar Sejarah Indonesia Baru; 1500-1900, Jilid I, (Jakarta: PT. Gramedia, 1987).